Enhancement of pore confinement caused by the mosaic structure on Ru nanoparticles for pH-universal hydrogen evolution reaction. Issue 7 (30th January 2023) - Ma, Xiaofang; Xiao, He; Gao, Yang; Zhao, Man; Zhang, Li; Zhang, Junming; Jia, Jianfeng; Wu, Haishun
Abstract : Stability enhancement of pore-confined Ru NPs embedded in porous carbon spheres for pH-universal hydrogen evolution reaction. Abstract : Design of efficient and stable hydrogen evolution reaction (HER) electrocatalysts for mass production of hydrogen via electrochemical water splitting is a challenging but urgent task. In this work, a highly dispersed Ru NP catalyst (Ru/HMCs-500) is built using a porous carbon sphere orifice embedded Ru nanoparticle (NP) method and shown to have extremely good HER stability and activity throughout the whole pH range. An ammonia concentration is applied to control the pore size of hollow mesoporous carbon spheres (HMCs) to confine Ru NPs. Noticeably, the mass activities of obtained Ru/HMCs-500 at −50 mV are 1.3 times, 7.0 times, and 3.8 times higher than that of Pt/C in acidic, basic, and neutral solutions, respectively. The characterization results reveal that Ru NPs with an embedded structure are restricted by pores. The high dispersion and anchoring effect ensure the long-term catalytic stability and activity of the catalyst. Metal–support strong interaction (SMSI) optimizes the electronic structure of Ru NPs, which greatly improves their intrinsic activity and reduces the activation energy of the HER. This work enlightens us on how to accurately construct the embedded structure of metal-based materials for enhancing the electrocatalytic HER performance in pH-universal solution.